LoRa SV611-Based Communication System To Monitor Behaviour of Rocket Using Inertial Measurement Unit Sensor - Misbahuddin, Misbahuddin; Taufik, Muhamat; Suksmadana, I Made Budi (International Journal of Electrical, Energy and Power System Engineering, 2022)
A payload is a material carried by a rocket that acts as telemetry, monitoring environmental conditions and transmitting them to earth-based receiving stations. The goal of this study is to design, build, and test a rocket payload monitoring system that will track the rocket's position, behaviour, and trajectory. The rocket payload and the Ground Control Station are designed and manufactured separately (GCS). The payload is made up of a variety of components, including an Arduino Uno, an MPU-6050 sensor, a GPS Neo-7M, and a LoRa SV611 transmitter. The GCS is made up of a raspberry Pi, a LoRa SV611 receiver, USB TTL, and python idle. Pitch, roll, yaw, longitude, latitude, and altitude are among the six characteristics that the rocket payload monitoring system can track. The results of the tests show the rocket payload monitoring system can track six parameters and trajectory in real time with a high degree of accuracy. All payload measurement parameters are clearly displayed in the GCS interface as graphs that are updated every 1000 milliseconds.